Characteristics of a global classification system for perinatal deaths: a Delphi consensus study. Issue 1 (December 2016) - Wojcieszek, Aleena; Reinebrant, Hanna; Leisher, Susannah; Allanson, Emma; Coory, Michael; Erwich, Jan; Frøen, J.; Gardosi, Jason; Gordijn, Sanne; Gulmezoglu, Metin; Heazell, Alexander; Korteweg, Fleurisca; et al.
Abstract Background Despite the global burden of perinatal deaths, there is currently no single, globally-acceptable classification system for perinatal deaths. Instead, multiple, disparate systems are in use world-wide. This inconsistency hinders accurate estimates of causes of death and impedes effective prevention strategies. The World Health Organisation (WHO) is developing a globally-acceptable classification approach for perinatal deaths. To inform this work, we sought to establish a consensus on the important characteristics of such a system. Methods A group of international experts in the classification of perinatal deaths were identified and invited to join an expert panel to develop a list of important characteristics of a quality global classification system for perinatal death. A Delphi consensus methodology was used to reach agreement. Three rounds of consultation were undertaken using a purpose built on-line survey. Round one sought suggested characteristics for subsequent scoring and selection in rounds two and three. Results The panel of experts agreed on a total of 17 important characteristics for a globally-acceptable perinatal death classification system. Of these, 10 relate to the structural design of the system and 7 relate to the functional aspects and use of the system. Conclusion This study serves as formative work towards the development of a globally-acceptable approach for the classification of the causes of perinatal deaths. The list of functional and structural characteristics identified should be taken into consideration when designing and developing such a system.